How do agricultural polders modulate nutrient dynamics under extreme flooding: Insights for water management in lowland areas - Hui Xie; Yunliang Li; Meiqi Shang; Jianwei Dong; Xiaoxian Tang; Nengsheng Wan; Yang Wang; Xijun Lai (Journal of Hydrology: Regional Studies)
Study region: Lake Chaohu Basin, a typical agricultural watershed with polders in lowland areas Study focus: Agricultural polders are typical agro-ecosystem units to prevent flooding in lowland areas worldwide. When facing extreme floods, they are also used to store floodwater temporarily. This function shift significantly affects nutrient dynamics and transport process, which, however, remains poorly understood. This study used field investigation and high-frequency monitoring to examine the nutrient dynamics modulated by agricultural polders in Lake Chaohu Basin, China when facing the extreme 2020 Yangtze River flood. New hydrological insight for the region: The results highlight the retention-reaction-remobilization function of agricultural polders to reduce nutrient pollution under extreme flooding. Inundated polders had lower concentrations of nitrogen (N) than protected polders, indicating the retention and reaction of N during inundation. Drained polders exhibited poorer water quality than inundated polders in terms of dissolved oxygen, N and phosphorus (P) concentrations, suggesting an increase of pollution during remobilization of the floodwater. However, such increase had little impact on the water quality of receiving rivers which showed generally better water quality than in early flood rising period. The above results indicated the buffering role of agricultural polders to mitigate nutrient pollution when facing extreme flooding. The outcomes from this study provide new insights into flood control strategies to integrate water quality restoration and sustainable agriculture in lowland areas.